Application of Interactive Media Techniques in Virtual Reality in the Marketing of Tourist Trails in Jordan - ALKURDI, Ibrahim; ALANANZEH, Omar A.; QADDHAT, Ranea Mohammed; HAIJAWI, Lubna S.; ALHASANAT, Sami A. (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023DO - 10.14505/jemt.14.4(68).18, 2023)
Virtual Reality Technology (VRT) has many advantages that contribute to many electronic applications in the marketing of tourist sites. In recent times, VRT has witnessed a huge development in electronic tourism. This study is conducted to identify the enormous potential provided by technology in marketing virtual tourist tails in Jordan through an electronic application interface that contains information on virtual tourist tails within the tourist and archaeological sites within a two- and three-dimensional display mechanism. As well as the possibility of displaying pictures of tourist and archaeological sites in different dimensions and drawing scales, which contributes to identifying the geographical pattern in the distribution of tourism services within tourist attractions using spatial analysis based on techniques, applications, and computer systems for the virtual world. The study relied on neighbourhood analysis, which relies on Virtual Reality technologies, hotspot correlation analysis, and other mapping tests within the ARCGIS 10.3 spatial analyser extension. The study aims to connect the virtual tourist tails within the tourist and archaeological sites to each other, providing the possibility of interactive navigation according to the predefined scenario.